DEBATING ABOUT SITUATIONAL LEADERSHIP - Carmen CÎRSTEA; Dumitru Constantinescu (Management & Marketing)
In this paper we analyzed the cirumstances of every day life which requires the need to adapt the leadership style. Leadership needs a lot of abilities and skills, including the capability to communicate. The paper deals with leader’s need of changing the style of leading as organizational circumstances change. The process is efficient only when the leaders and the followers have the right climate. The importance of this process is reflected in the productivity of the organization. As the economic climate changes the leadership style needs to be changed and also the style of communication throughout the leader coaches, coordinates, evaluates and supervises. Leadership is about organizing a group of people to achieve a goal. The leader may or may not have any formal authority. Students of leadership have produced theories involving traits, situational interaction, function, behavior, power, vision and values, charisma, and intelligence, among others. This paper describes the styles of leadership which the leaders must use and switch when is needed in comparison with what leadership is about.